1989
DOI: 10.1111/j.1768-322x.1989.tb00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased biosynthesis of actin and cellular fibronectin during adipose conversion of 3T3‐F442A cells. Reorganization of the cytoarchitecture and extracellular matrix fibronectin

Abstract: Differentiation of 3T3-F442A cells was accompanied by changes in cell morphology, decreased synthesis and assembly of actin and fibronectin. The network of microfilament stress fibers detected with NBD-phallacidin was altered during adipose conversion of 3T3-F442A cells. Parallel to this, the disappearance of fibrillar bundles of extracellular matrix fibronectin was observed by immunofluorescence staining. The pericellular fibronectin content, detected by immunoblotting, strongly diminished during the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 33 publications
5
28
0
1
Order By: Relevance
“…Similar results were reported using 3T3 cells [1,22]. It is interesting that cells on fibronectin have small amounts of cytoplasmic lipid droplets though covered with the secondary collagen layer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were reported using 3T3 cells [1,22]. It is interesting that cells on fibronectin have small amounts of cytoplasmic lipid droplets though covered with the secondary collagen layer.…”
Section: Discussionsupporting
confidence: 76%
“…Kuri-Harcuch et al pointed out that the differentiation of 3T3-F442A cells accompanied the production of ECM [14]. Antras et al [1] and Fernandez and Ben-Ze'ev [9] reported the inhibitory effect of fibronectin on the differentiation of 3T3-F442A cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with previously published mRNA data from human [23,24], but not rat adipose tissue [29]. As preadipocytes change the expression of classic "housekeepers" like actin during adipose conversion [30], γ-tubulin was therefore chosen as loading control. …”
Section: Ace Protein Expression In Human Primary Preadipocytes and Dusupporting
confidence: 81%
“…However, less attention has focused on the modulations in cytoskeletal and ECM components accompanying adipocyte differentiation. During differentiation, expressions of actin, tubulin, fibronectin, type I and type III collagen, and pref-1 decrease whereas expressions of CSPG-1, entactin/nidogen, and type IV collagen increase (Spiegelman and Farmer, 1982;Aratani and Kitagawa, 1988;Antras et al, 1989;Weiner et al, 1989;Calvo et al, 1991;Smas and Sul, 1993). Among these, collagen is the major ECM protein and shown to drastically decrease in mRNA level by 80-90% during 3T3-L1 differentiation (Weiner et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Besides significant increases in mRNAs of the genes directly involved in lipidogenesis, changes occur in expression of cytoskeletal, extracellular matrix (ECM), and related components such as actin, tubulin, fibronectin, and collagen (Spiegelman and Farmer, 1982;Antras et al, 1989;Weiner et al, 1989). Modulation of cytoskeletal and ECM components could allow for cytoskeletal rearrangement, release of cell adhesion, and remodeling of cell components necessary for morphological changes.…”
Section: Introductionmentioning
confidence: 99%